PENGARUH LOKASI, SUASANA CAFE, DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN - Sriyani Sriyani; Unna Ria Safitri; Nuning Lisdiana (Universitas Boyolali, 2022)
ABSTRACT “This study aims to determine the influence of location, café atmosphere and social media on the purchasing decisions of Waroeng Damandiri Selo Boyolali consumers. The data collection technique for distributing questionnaires with a sample of 100 respondents used the Accidental sampling method”. The research methods used are quantitative methods and descriptive analysis of case studies. Testing data instruments with validity and reliability tests, data analysis used normality tests, multi choline therapy tests, heteroscedasticity tests, autocorrelation tests with durbin Watson tests and hypothesis tests to find out between variables have a significant relationship. the results of the t-test study ( partial ) obtained tcount the location variable 0.934 < 1984 and a significant value of 0.353 > 0.05 which means insignificant. So Ho was accepted and Ha was rejected. The café atmosphere variable resulting from the calculation of the t-test ( partial) obtained 15 tcount, the café atmosphere variable 0.955 < 1.984 and the significant value 0.342 > 0.05 which means insignificant. And the social media variable obtained t-test calculation ( partial) obtained calculate the social media variable 6,174 >1,984 and a significant value of 0.000 < 0.05 which means significant. The results of the F test (simultaneous) obtained Fcounted 53,964 > 2.70 using a α (alpha) level of 0.05 or 5% then Ho was rejected and Ha was accepted. it can be concluded that all independent variables simultaneously affect the dependent variables. Keywords : Location, Cafe Atmosphere, Social Media and Purchasing decisions